The association of sleep problem, dietary habits and physical activity with weight status of adolescents in Nepal - Devendra Raj Singh; Dev Ram Sunuwar; Babita Dahal; Rajeeb Kumar Sah (BMC, 2021)
Abstract Background Overweight/obesity among adolescents is an emerging public health issue worldwide. However, the evidence on the determinants of body weight status and lifestyle behaviors among Nepalese adolescents is limited. This study aims to explore the sleep characteristics, dietary habits, and physical activity and its association with body mass index (BMI) among Nepalese adolescents. Methods A cross-sectional study was conducted between July and November 2019 among 627 randomly selected adolescents from eight schools located in Kathmandu Metropolitan City, Nepal. A self-administrated structure questionnaire was used to collect the data. Anthropometric measurements (adolescent's BMI), sleep characteristics, dietary habits, and physical activity were assessed using validated tools. Multinomial logistic regression analyses assessed the association between covariates and BMI categories. The statistical significance was considered at p-value < 0.05 and 95% confidence intervals (CIs). Results The overall prevalence of underweight and overweight/obesity among adolescents was 9.1% (95% CI: 7.1-11.6) and 23.7% (95% CI: 20.6-27.7) respectively. In multinomial logistic regression, adolescents who reported sleep problem compared to those with no such problem (Relative risk ratio (RRR) = 13.37, 95% CI: 7.14-25.05), adolescents who had obstructive sleep apnea (OSA) symptoms (RRR = 3.21, 95% CI:1.31-7.86), who consumed soft drink ≥1 time/day in past 1 months (RRR = 5.44, 95% CI: 2.93-10.10), consumed high-fat dietary ≥2 times/day (RRR = 2.17, 95% CI: 1.18-3.99), and had a habit of junk food consumptions (RRR = 5.71, 95% CI:2.55-12.82), adolescents who had 5-6 h/day sedentary behavior (RRR = 3.21, 95% CI: 1.14-9.09), adolescents from Terai/Madhesi castes (RRR = 2.81, 95% CI: 1.19-6.64) and adolescents whose father was employed (RRR = 2.04, 95% CI: 1.04-3.98) were at increased risk of being overweight/obesity. In contrast, adolescents aged 14-16 years had 71% lower (RRR = 0.29, 95% CI: 0.16-0.52), and adolescents who consumed less than five food groups had 45% lower (RRR = 0.55, 95% CI: 0.31-0.97) risk of being overweight/obesity compared to 12-14 years age groups and consumed more than five food groups respectively. Conclusions The findings of this study warrant immediate interventions to improve the lifestyle to reduce overweight/obesity among Nepalese adolescents. Creating a conducive environment, both at school and home is essential to encourage adolescents for the adoption of healthy lifestyle behaviors.